PRELIMINARY PHYTOCHEMICAL ANALYSIS AND IN VITRO ANTIOXIDANT ACTIVITY OF ARAUCARIA COLUMNARIS BARK PEEL AND COSMOS SULPHUREUS FLOWERS - Jadav, Krishma M.; Gowda, K. N. Ninge (International Journal of Current Pharmaceutical Research, 2017)
Objective: Four different extracts of Araucaria columnaris (bark peel) and Cosmos sulphureus (flowers) were screened for their phytochemical composition, and free radical scavenging activities. Methods: DPPH method was used to test the antioxidant activity for extracts. Results: Among the different extracts tested, the methanol extract of both the plant species showed significant radical scavenging activities. Phytochemical analysis of the extracts revealed that the radical scavenging activities might be due to the presence of flavonoids, tannins and phenolic compounds. Conclusion: The results obtained suggest that Araucaria columnaris (bark peel) and Cosmos sulphureus(flowers) could be exploited in the treatment of various diseases like cancer, cardiovascular diseases and infection diseases.Â  Â 